2007
DOI: 10.1007/s10661-007-9615-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening of δ-aminolevulinic acid dehydratase from Pseudomonas strains as biosensor for lead and some other metals contamination

Abstract: delta-Aminolevulinic acid dehydratase (ALAD; E.C. 4.2.1.24) is a metalloprotein and plays a crucial role in heme synthesis. Its sensitivity to toxic metals depends on the metallic co-factors. In this study the effects of some heavy metals on ALADs activity of five Pseudomonas isolates from Akarçay stream (Afyonkarahisar) have been studied in order to determine whether their ALADs could be used as biosensor for lead and other heavy metals contamination. The data obtained from the study were analysed statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The dehydration of alcohols yielding alkenes is a very significant biochemical reaction which plays an important role in the citric acid cycle . Furthermore, dehydratase enzymes, such as 3-hydroxyacyl ACP dehydratase or δ-aminolevulinic acid dehydratase, also play a crucial role in fatty acid and heme synthesis. PCV TP233 was further transformed by oxidation of the aldehyde moiety to the respective carboxylic acid (PCV TP249B) or underwent hydration yielding PCV TP251. Even though the exact position of the hydroxyl group could not be assigned in PCV TP251 as no NMR spectra were available due to the limited quantity isolated, it is likely that the hydroxyl group is located at the methyl group of the side chain which has also been observed for the hydration of acrolein yielding 3-hydroxypropanal. , However, none of the identified TPs were detected during incubation of PCV TP251, which was dissipated after 240 h. This might indicate that the hydroxyl group introduced during hydration of PCV TP233 is not located at the methyl group as proposed above but at the tertiary carbon.…”
Section: Resultsmentioning
confidence: 99%
“…The dehydration of alcohols yielding alkenes is a very significant biochemical reaction which plays an important role in the citric acid cycle . Furthermore, dehydratase enzymes, such as 3-hydroxyacyl ACP dehydratase or δ-aminolevulinic acid dehydratase, also play a crucial role in fatty acid and heme synthesis. PCV TP233 was further transformed by oxidation of the aldehyde moiety to the respective carboxylic acid (PCV TP249B) or underwent hydration yielding PCV TP251. Even though the exact position of the hydroxyl group could not be assigned in PCV TP251 as no NMR spectra were available due to the limited quantity isolated, it is likely that the hydroxyl group is located at the methyl group of the side chain which has also been observed for the hydration of acrolein yielding 3-hydroxypropanal. , However, none of the identified TPs were detected during incubation of PCV TP251, which was dissipated after 240 h. This might indicate that the hydroxyl group introduced during hydration of PCV TP233 is not located at the methyl group as proposed above but at the tertiary carbon.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, ALAD is most popular one, and its results showed good combination with the blood Pb level determined by atomic absorption spectrophotometry or ICP. There are some mathematical equations deviced by several authors to give the Pb concentration by looking at the activity of ALAD (Ogunseitan 1999, Ogunseitan et al 2000, Korcan et al 2007. The expression of ALAD activity gives us a clear indication of the severity of the effect of Pb pollution along the pollution gradient.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the enzymes obtained from yeast (Saccharomyces cerevisiae), Escherichia coli and plants have slightly higher alkali optimal pH. It was reported that S. cerevisiae, E. coli, Streptomyces yokosukanensis ATCC 25520, and Pisum sativum optimal pHs were 9.8, 8.5, 8.0, and 8.0, respectively Konuk et al 2008;Korcan et al 2007;Ogunseitan 1999;Senior 1996). Chauhan et al (1997) show that wild-type Bradyrhizobium japonicum ALAD had a high pH optimum for activity of at least 9.5, whereas the modified enzyme designated ALAD showed a sharp pH optimum of 6.…”
Section: Resultsmentioning
confidence: 99%
“…A certain amount of crude enzymic extract including 100 μl metal solutions [500 μM of Pb, Ni, Zn, Co, Mn, and Mg] was incubated for 1 h at 27 • C. After the incubation, ALAD activities were determined (Battistuzi et al 1981;Konuk et al 2008;Cigerci et al 2008;Korcan et al 2007). A control experiment without metals was conducted and all experiments were triplicated.…”
Section: Effects Of Various Metals On Alad Activitymentioning
confidence: 99%
See 1 more Smart Citation